RESEPSI SISWA MADRASAH TSANAWIYAH KABUPATEN BANTUL TERHADAP CERPEN REMAJA PADA SURAT KABAR KEDAULATAN RAKYAT - Yuniati, Siska; Nurgiyantoro, Burhan (Sunan Kalijaga State Islamic University Yogyakarta, 2019)
Literary reception encompasses reader’s role in making meaning from literary texts. Student’s reception of teenage short story can give an idea of student’s acceptance of this type of text. This is interesting because students as teenagers are rarely involved in responding to teenage short stories, particularly ones available in newspapers. This research aims to examine the reception of teen short stories in the Kedaulatan Rakyat Newspaper by students of Madrasah Tsanawiyah in Bantul Regency in terms of intellectual and emotional aspects. Respondents in this study are 128 students of MTsN 1 Bantul, MTsN 3 Bantul, MTsN 4 Bantul, MTs Al Falah, and MTs Hasyim Asy'ari. The data were collected using a reception questionnaire focusing on intellectual and emotional aspects. The results of the study are as follows. First, in terms of intellectual aspect, the students’ reception of teen short stories in Kedaulatan Rakyat is high (70.82%), moderate (15.62%), and low (13.58%). Second, in terms of emotional aspect, the students’ reception of teen short stories in this newspaper is high (38.86%), moderate (20.28%), and low (40.86%). Fourth, there is no significant difference between the reception of students from state madrasah and private madrasah. Based on the results of this study, it can be concluded that students of class IX of Madrasah Tsanawiyah, Bantul Regency can understand well the elements of story builders and the structure of short story, language, themes, and conflicts in the short story. Students also understand the logic of the story in the text and feel the tension of the conflict. The new values in the short stories and actions of the main characters are quite acceptable to students. Students are also interested enough to discuss the short stories further. Meanwhile, most students felt less emotional impact and do not feel the tension presented in the short story.